Ru0·Run+/Al2O3 as a Versatile Catalyst in the Isomerization of Allyl Alcohol - Enciso, Julián; Ramírez, Alfonso; Ostos, Carlos; Echavarría, Adriana; Córdoba, Misael; Lederhos, Cecilia; Miranda, Cristian (Frontiers in Chemistry, 2021)
This study focuses on examining the isomerization of allyl alcohol using ruthenium (Ru) supported on alumina as a heterogeneous catalyst. The synthesized Ru/Al solids were characterized by various characterization techniques. The content of Ru was estimated by the energy dispersive x-ray technique. The x-ray diffraction (XRD) confirmed the presence of phases in the support and active species in the catalysts. The surface area of the support after Ru impregnation and the pore volume were determined by nitrogen physisorption. The analysis of programmed temperature (TPR and TPO) shows different redox sites which is confirmed by XPS. The catalytic results suggest a dependence on the amount of available metallic Ru, as well as the importance of the continuous regeneration of the metal using H2 to achieve a good conversion of the allyl alcohol. For comparison purposes, the commercial Ru on alumina 5% (CAS 908142) was used. The results show up to 68% alcohol conversion and 27% yield of the isomerization product using Ru(1,5.4h)/Al catalyst in comparison with 86% conversion and 39% yield of the isomerization product using CAS 908142. In contrast, our catalysts always presented higher TOF values (149–160) in comparison with CAS 908142 (101).